Dye-sensitized solar cells based on dimethylamino-π-bridge-pyranoanthocyanin dyes. (August 2020) - Pinto, Ana Lucia; Cruz, Hugo; Oliveira, Joana; Araújo, Paula; Cruz, Luis; Gomes, Vânia; Silva, Cassio P.; Silva, Gustavo T.M.; Mateus, Tiago; Calogero, Giuseppe; de Freitas, Victor; Quina, Frank H.; et al.
Graphical abstract: Highlights: pH shows impact through modulation of 'Dual-mode anchoring' (OH vs. amino) to TiO2 . Efficiencies of 2.37% achieved with compounds anchoring through a single OH unit. Increase in π-conjugation through CC bonds diminished electron-donor ability. Abstract: The pyranoanthocyanins present in red wine display great potential as photosensitizers in bio-inspired Dye-Sensitized Solar Cells (DSSCs). Following a biomimetic approach, a series of amino-π-bridge-pyranoanthocyanin derivatives were employed as dye sensitizers in DSSCs. The dimethylamine group was selected to take advantage of its electron-donor character and the possibility of 'dual-mode anchoring' (OH vs. dimethylamino) to titanium dioxide. The increase in π-conjugation via insertion of CC bonds affected molecule flexibility, electron-donor ability and the pH-dependent equilibria of the pyranoanthocyanin derivatives. The current vs . potential properties of photoanodes using these dyes pointed to essential features of the relationship between power conversion efficiency and dye structure. These included the influences of the dimethylamine group, of π-conjugation and of substitution in ring B on the adsorption of the dyes to TiO2 and on the overall performance of the DSSCs prepared from them with and without added acid. An overall efficiency of 2.55% was obtained for the best performing compound, 4-(dimethylamino)-cinnamyl-pyranocyanidin-3- O -glucoside (JO3 ), which consolidates the importance of this family of compounds as potential dye-sensitizers for DSSC applications.